Variations in Alginate Concentration as a Material for Immobilizing Thermophilic Bacteria on the Characteristics of Beads - Summaiati, Titi; Irdawati, Irdawati (Jurnal Serambi Biologi, 2024)
Immobilization is a technique for physically confining or placing microbial cells in a certain space, where the cells still maintain catalytic activity. The cell immobilization technique aims to facilitate product purification, increase productivity, make it easier to control cell stability and microbial cells can be used repeatedly. One carrier that is often used as a matrix to trap microorganism cells is alginate. Alginate is a type of polysaccharide obtained through extraction from brown algae. The immobilization technique with aginate cells was chosen because of its non-toxic nature, simple procedure for immobilization and cheap price for industrial applications. Alginate concentration affects the physical and chemical properties of the beads produced, such as size, shape and color of the beads. This study aims to compare variations in alginate concentration as a material for immobilizing thermophilic bacteria on the characteristics of the beads. This research is descriptive research. Beads are made with varying concentrations, namely 2%, 3%, 4%, 5% and 6% alginate. Data in the form of beads characteristics which include size, shape and color of beads. Based on research, the results obtained are that the higher the alginate concentration, the larger the diameter of the beads, the color of the beads will be more intense and the shape of the beads will tend to be round, and the beads will be sturdier, and vice versa.